2017
DOI: 10.1002/anie.201700424
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative LC–MS Provides No Evidence for m6dA or m4dC in the Genome of Mouse Embryonic Stem Cells and Tissues

Abstract: Abstract:Until recently,i tw as believed that the genomes of higher organisms contain, in addition to the four canonical DNAb ases,o nly 5-methyl-dC (m 5 dC) as am odified base to control epigenetic processes.I nr ecent years,t his view has changed dramatically with the discovery of 5-hydroxymethyldC (hmdC), 5-formyl-dC (fdC), and 5-carboxy-dC (cadC) in DNAfrom stem cells and brain tissue.N 6 -methyldeoxyadenosine (m 6 dA) is the most recent base reported to be present in the genome of various eukaryotic organ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
84
0
2

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 121 publications
(107 citation statements)
references
References 24 publications
10
84
0
2
Order By: Relevance
“…Using this approach, we found that up to 15% of reads in published samples of 6mA-DIP-seq in mammals mapped to the Mycoplasma genome 31 . Taken together with the results of a recent study that was unable to detect 6mA in mammalian cells using mass spectrometry and our results showing clear enrichment for STRs using the 6mA antibody, a re-evaluation of the extent and origin of 6mA in mammalian studies is advisable 34 . As many bacteria and viruses contain abundant amounts of modified bases including 5mC, 5hmC and 6mA, controlling for contaminating DNA in all DIP-seq assays requires more rigorous application, particularly when the genomic content of target modifications in mammals becomes increasingly rare.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Using this approach, we found that up to 15% of reads in published samples of 6mA-DIP-seq in mammals mapped to the Mycoplasma genome 31 . Taken together with the results of a recent study that was unable to detect 6mA in mammalian cells using mass spectrometry and our results showing clear enrichment for STRs using the 6mA antibody, a re-evaluation of the extent and origin of 6mA in mammalian studies is advisable 34 . As many bacteria and viruses contain abundant amounts of modified bases including 5mC, 5hmC and 6mA, controlling for contaminating DNA in all DIP-seq assays requires more rigorous application, particularly when the genomic content of target modifications in mammals becomes increasingly rare.…”
Section: Discussionsupporting
confidence: 80%
“…2f). Contamination of these samples may explain the earlier detection of 6mA in mammalian samples by mass spectrometry 31 and the subsequent failure of more recent attempts to detect 6mA in mammalian DNA using ultrasensitive UHPLC-MS 28,34 .…”
Section: Igg Binding Of Dna Repeats Explains the Conflicting Results mentioning
confidence: 99%
“…[145][146][147][148][149] While the levels of m 6 dA are high in unicellular eukaryotes (ciliated protozoa and green algae), they are extremely low in all higher eukaryotes studied so far. They are so low that ar ecent ultrasensitive LC-MS 2 based approach, using an isotopically labelled m 6 dA standard, was unable to confirm the presence of m 6 dA in vertebrates.T his result questions whether m 6 dA is af requently present and epigenetically relevant base, [150] but it cannot be excluded that m 6 dA is formed as aD NA lesion or during certain developmental phases.T he idea that m 6 dA is formed as al esion could explain the requirement for an m 6 dA demethylase. [144,147] One study showed recently as harp peak of m 6 dA content in early embryos of zebrafish and pig, [148] hinting indeed at an internal source of m 6 dA.…”
Section: Discovery Of Oxidized Bases Beyond Hmdcmentioning
confidence: 98%
“…Although most studies have reported vanishingly low 6mdA levels in mammals (0.0001 to 0.01% 6mdA/adenine), the range of reported 6mdA abundance between mammalian species and tissues is considerable (0.0001 to 1% 6mdA/dA; range, ~10,000-fold) (4,(6)(7)(8)(9)(10). In contrast, several other studies have been unable to detect 6mdA in mammals using highly sensitive methods (11)(12)(13). While the function of 6mdA in mammalian DNA is currently unknown, reports have suggested a potential role for 6mdA in lineage specification (8,9), similar to the role of its RNA counterpart, N 6 -methyladenosine (m 6 A) (14).…”
Section: Introductionmentioning
confidence: 99%